Metal-matrix composite materials: Manufacturing and joining methods - FERİK, ERMAN (NOVA Science Publishers Inc., 2022)
Composite materials are solid materials produced by combining two or more components to provide the required properties. Metal-matrix composites (MMCs) are composite materials that have at least two component materials, one of which is metal (Al, Mg, and Cu etc.), the other component material may be a different ceramic or another material such as metal. The development of MMCs has reflected the need to achieve combinations of properties (wear resistance, fatigue resistance, thermal properties, etc.) beyond those achievable with metals alone. MMCs are used in aerospace, defense, automotive, etc. It is widely used in industrial areas.Nanoceramic particles (carbides, oxides, nitrides and carbon nanotubes) such as SiC and Al2O3 are generally added to MMCs as particulate additives. Particulate additives are commonly used to reinforce the metal-matrix, providing the matrix material with high hardness, strength, hardness and wear resistance. Fine fiber additives are more effective than particulate additives, but their using are generally costly. The interface between the additives and the matrix has a very important place in determining the properties of MMCs. In many MMCs, a thin coating must be applied over the additives before the additives areincorporated into the metal-matrix. These coatings are applied for reasons such as promoting wetting and bonding between fiber additives and matrix material. The manufacturing techniques used for the production of MMC materials and their components depend on the types of matrix and additives to be produced; they are classified according to whether the matrix is solid, liquid or gaseous when combined with the additive. Each of these production methods has advantages and disadvantages. As it is known, the use of MMC materials is becoming more and more common day by day. For this reason, MMC materials must be defined correctly. In this section, the current state of MMC is given. Production methods and systems of MMCs, matrix and reinforcement materials, conventional, solid state and other welding methods are discussed.
Keywords: Metalurji ve Malzeme Mühendisliği; Malzeme Bilimi ve Mühendisliği; Birleştirme; Kompozitler; Metalik Malzemeler; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Material science and engineering; Joining and Cutting; Composites; Metallic Materials; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING